2016
DOI: 10.4103/0970-0358.182236
|View full text |Cite
|
Sign up to set email alerts
|

Management of fourth degree obstetric perineal tear without colostomy using non - stimulated gracilis - our experience over eleven years

Abstract: Background:Although gracilis muscle transposition for faecal incontinence has been well-described method, its literature for use in obstetric perineal tear without colostomy is sparse. In this study, we have tried to analyse its use in fourth-degree obstetric perineal tears.Patients and Methods:A total of 30 patients with recto-vaginal fistula with faecal incontinence secondary to obstetric perineal tear were retrospectively studied between February 2003 and May 2014. The recto-vaginal fistula was explored, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The characteristics of the included studies are reported in Table 1. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Of the 20 included studies, 19 were case series (18 retrospective, 1 prospective), whereas 1 was a prospective cohort study. Six studies (30%) included only our population of interest [21][22][23][24][25][26] ; 11 studies (55%) also included other types of fistulas [27][28]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The characteristics of the included studies are reported in Table 1. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Of the 20 included studies, 19 were case series (18 retrospective, 1 prospective), whereas 1 was a prospective cohort study. Six studies (30%) included only our population of interest [21][22][23][24][25][26] ; 11 studies (55%) also included other types of fistulas [27][28]…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Of the 20 included studies, 19 were case series (18 retrospective, 1 prospective), whereas 1 was a prospective cohort study. Six studies (30%) included only our population of interest [21][22][23][24][25][26] ; 11 studies (55%) also included other types of fistulas [27][28][29][30][31][32][33][34][35][36][37] and 3 studies (15%) also included other interventions. [38][39][40] The risk of bias evaluation is reported in Table 2 and Supplemental Figure 1 patients; 26%), complications from previous pelvic surgery (78 patients; 20%), and obstetric injury (73 patients; 19%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations